Application of ERAS concept in clinical nursing of patients with advanced cancer pain of gynecological malignant tumors - Liao, Haijing; Lei, Yuanxiu (Frontiers in Oncology, 2023)
Gynecological malignant tumor refers to the malignant tumor of organs and tissues centered on the uterus, ovary and fallopian tube. Among gynecological tumors, endometrial cancer is the most malignant, accounting for more than 80% of female reproductive tract malignant tumors. The common symptoms are vaginal bleeding and pain. The pain of gynecological cancer patients can be divided into physiological pain and pathological pain. Physiological pain is a physiological reaction caused by the stimulation of the body, which does not affect the daily life of patients. Pathological pain mainly refers to physical pain caused by organic diseases or psychological factors, such as cancer pain caused by advanced malignant tumors and cancer pain caused by various reasons. The purpose of this article is to explore the application and analysis of ERAS (enhanced recovery after surgery) concept in the clinical nursing of patients with advanced cancer pain in gynecological malignancies. This paper analyzed the pain caused by advanced cancer, proposed ERAS multimodal analgesia method, and used image fusion technology to detect cancer patients. At the end of this paper, the clinical nursing of ERAS concept in the treatment of advanced cancer pain of gynecological malignant tumors was explored experimentally. The results of this study showed that in terms of pain impact score, before treatment, the score of group M was 39.07, and the score of group N was 38.92, with no significant difference. The score after ERAS concept treatment was 58.14, while the score after traditional treatment was 43.79, with a significant difference. The results showed that the pain impact score after treatment was significantly due to the pre-treatment, and the improvement effect of ERAS concept treatment was more obvious.